EVALUATION OF TRANSPORT STRESS ON GROWER PIG AND ITS MANAGEMENT (Indian Journal of Animal Production and Management, 2014)
An investigation was carried out to evaluate the effect of transport stress in pigs. Twenty five Large White Yorkshire grower pigs of 60-70 days age were transported from Haringhata Farm, Mohanpur, West Bengal to National Research Centre on Pig, Guwahati, Assam (1185 Kms). The body weight and blood samples of animals were taken at the time of loading the animals, unloading of animals, 3 days after unloading and 10 days after unloading without exerting any stress on the animals. There was significant loss in body weight of the transported pigs which can be attributed to stress and also reduced feed intake (0.75 versus 1.04 Kg). By 10 days rest in the quarantine shed, animals were able to recoup its normal feed intake. Similar trend was observed with the stress biomolecules, like Lactate Dehydragenase, SGOT and SGPT which was increased significantly during the period of stress. This study showed that the transportation of pigs over longer durations results in increased physiological stress on pigs and as longer durations (24-36 hours) of transport generally produced more significant results.
Keywords: Transport stress; Pig; enzymes